Plastic damage evolution in multilayer coatings/ductile substrate system under spherical indentation: Influence of a metallic interlayer - Quy, Le Minh; Thinh, Tran Ich (Vietnam Journal of Mechanics, 2005)
Spherical indentation problems of ceramic coatings/metallic inter-layer/ductile substrate were investigated numerically by axisymmetric finite element analysis (FEA) for two typical ceramic coatings with relatively high and low elastic modulus deposited on aluminum alloy and carbon steel. Various indenter radius-coating thickness ratios and interlayer thickness-coating thickness ratios were used in the modeling. Plastic damage zone evolution were discussed in connection with model parameters. The results’ showed that the suitable metallic interlayer could improve resistance of ceramic coating systems through reducing the plastic damage zone size in the substrate under spherical indentation.